Analisa Pengaruh Variasi Voltage dan Perbedaan Kawat Las GMAW terhadap Cacat Las pada Sambungan Fillet T Joint menggunakan Visual Test dan Penetrant Test - Lintang Firdaus Romadhoni; Fica Aida Nadhifatul Aini (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
The welding process is a crucial element in the fabrication and manufacturing industries, serving to join two or more components into a single unit. The quality of the weld is very important, but defects such as undercut, underfill, and spatter are often still found. This study aims to analyse welding defects caused by voltage variations and differences in welding wire on T-joint fillet welds using the Gas Metal Arc Welding (GMAW) method on 8 mm thick plates. The voltage variations used were 20.6 V, 23.7 V, and 27.9 V, with welding wires EN ISO 14341-A: G 42 4 M21 3Sil and EN ISO 14341-A: G 46 4 M21 Z 3Ni1Cu. The research method used visual inspection and penetrant testing to identify types of welding defects. The research results showed four types of welding defects from visual inspection: spatter, undercut, weld deposit thickness, and excessive throat thickness, and two from penetrant testing: undercut and end creater pipe. Based on the two tests conducted in this study, it can be concluded that the optimal welding results were achieved at a voltage variation of 23.7 V using the EN ISO 14341-A: G 46 4 M21 Z 3Ni1Cu, as it had the fewest welding defects. The worst welding results were obtained at a voltage variation of 20.6 V using both types of welding wire, as this welding process resulted in numerous welding defects in both visual and penetrant testing. This study provides insights that proper welding parameter settings significantly influence the quality of the welded joint.